School-Based Management Strategies in Enhancing Teacher Welfare and Social Competence in Elementary Schools - Hasrinaldi Hasrinaldi; Rahmattullah Rahmattullah; Muhammad Iqbal (Journal of Educational Sciences, 2026)
School-Based Management (SBM) promotes school autonomy and stakeholder participation in managing educational resources to improve school quality. This study aims to analyze SBM strategies in enhancing teacher welfare and social competence at SDN 4 and SDN 10 Tapak Tuan, Aceh Selatan. A qualitative case study approach was employed to explore SBM implementation in authentic school settings. Data were collected through participatory observation, in-depth interviews, and document analysis involving principals, teachers, school committee members, and supervisors. The findings indicate that SBM improves teacher welfare through participatory decision-making, transparent financial management, and strengthened collaboration with stakeholders. In addition, SBM fosters teachers’ social competence by promoting collegial teamwork, effective communication, and active engagement within the school community. Although challenges such as limited funding and workload demands persist, adaptive leadership and collaborative support contribute to sustainable implementation. In conclusion, SBM functions as a strategic framework for empowering teachers and strengthening professional capacity, thereby supporting quality improvement in elementary education.